Role of the YWHAG gene mutations in Developmental and Epileptic Encephalopathy - Vilmont, Violet; Nowakowski, Richard S.; Zhou, Yi (Frontiers in Neuroscience, 2025)
Developmental and Epileptic Encephalopathy (DEE) is a severe neurological condition characterized by epileptic seizures and cognitive developmental impairments. Mutations in the YWHAG gene, which encodes the 14-3-3γ protein, are implicated in DEE. Predominantly expressed in the brain, 14-3-3γ regulates various cellular processes, forming homodimers or heterodimers with other isoforms. It binds to phosphorylated sites on target proteins, influencing their activity, stability, or cellular localization. This review evaluates the association between YWHAG mutations and DEE, the mechanisms by which 14-3-3γ influences neuronal function, and potential therapeutic interventions. YWHAG mutations, often de novo, lead to a variety of epilepsy phenotypes, from febrile seizures to severe epileptic encephalopathies. Loss-of-function mutations disrupt neuronal homeostasis, contributing to epilepsies and cognitive dysfunction. Specific missense mutations in the 14-3-3γ, such as Arg132Cys, significantly impair the protein’s binding affinity and are associated with a severe DEE. These mutations impact the function and stability of 14-3-3γ, affecting its interaction with ion channels and proteins, thereby contributing to neuronal hyperexcitability and impaired development. Understanding the involvement of YWHAG in DEE can provide insights into targeted treatments that address both the epileptic and developmental components of the disorder.